Truck queuing analysis at landfill sites in a waste collection vehicle routing problem - Benjamin, Aida Mauziah; Ku-Mahamud, Ku Ruhana; Idrus, Zanariah (2017)
This paper presents an analysis of a truck queuing problem at landfill sites due to a static rest time of truck drivers in a waste collection vehicle routing problem. The analysis is based on a solution of two datasets from a benchmark waste collection problem using the nearest greedy heuristic algorithm.In this problem, all drivers need to have a one-hour rest break during their collection.The rest break can start from 11.00 a.m. to 12.00 p.m. However, based on the solution from a previous study, all drivers have their rest break almost at the same time. Consequently, all drivers travelled to landfill sites to unload waste approximately at the same time.Based on the truck queuing analysis presented in this paper, there is a long queue at landfill site 3 (ten trucks arrived between 2.52 p.m. to 2.53 p.m.) for dataset 1; whereas for dataset 2, 13 trucks arrived at landfill site 1 between 4.10 p.m. to 4.55 p.m. Thus, it may be concluded that the static rest time period of truck drivers can cause truck queuing at landfill sites. Long queues at landfill sites will increase the service time at landfill sites as well as affect the drivers’ arrival time at customers. This paper suggests that future works need to consider a dynamic rest time period in solution techniques to overcome the truck queuing problem at landfill sites for solving the waste collection vehicle routing problem.